2020
DOI: 10.3390/toxins12090582
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Sensitive Nanocomplex for Targeted Delivery of Melittin

Abstract: Although peptide therapeutics have been explored for decades, the successful delivery of potent peptides in vitro and in vivo remains challenging due to the poor stability, low cell permeability, and off-target effects. We developed a redox sensitive polymer-based nanocomplex which can efficiently and stably deliver the peptide drug melittin for cancer therapy. The nanocomplex selectively targets cancer cells through lactobionic acid mediated endocytosis and releases melittin intracellularly upon the trigger o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
(39 reference statements)
2
25
0
Order By: Relevance
“…These findings are consistent with some previous studies indicating melittin has poor cell selectivity [13,30]. The result of the hemolysis assay was also consistent with previous studies in which melittin showed massive hemolytic activity, indicating HD 50 ranged from 0.5 µg/mL to 2.84 µg/mL [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with some previous studies indicating melittin has poor cell selectivity [13,30]. The result of the hemolysis assay was also consistent with previous studies in which melittin showed massive hemolytic activity, indicating HD 50 ranged from 0.5 µg/mL to 2.84 µg/mL [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…They suggested that seasonal and environmental factors should be considered to obtain the highest melittin content from the bee venom. Second, to maximize the anticancer effect of melittin, Cheng and Xu [ 10 ] demonstrated a method to deliver melittin more efficiently and stably by developing a redox-sensitive polymer-based nanocomplex. They reported that polymer/melittin nanocomplexes showed increased cytotoxicity compared to free melittin.…”
mentioning
confidence: 99%
“…Multiple stimulus-responsive nano delivery systems have been used to deliver MEL to attenuate the cytotoxicity of MEL during systemic circulation and to achieve its targeted delivery, including pH-responsive [ 101 , 102 , 103 ], magnetic-responsive [ 84 ], photosensitive [ 103 , 104 ] and redox-sensitive [ 105 ] delivery systems. The stimulus-responsive carrier maintains a stable state during circulation in the body and is stimulated and changes conformation or structure when the nanocarrier reaches the target site and releases MEL to a therapeutic concentration [ 84 , 101 , 104 ].…”
Section: Delivery Vehicles For Melittinmentioning
confidence: 99%